Persepsi Peserta Didik terhadap Video Animasi Islami sebagai Alternatif Pembelajaran PAI dan Budi Pekerti di SDN 1 Air Putih Ulu Kabupaten Musi Banyuasin - Ike Nur Azizah; Sayid Habiburrahman; M Jauhari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The purpose of this study was to examine the opinions of students at SD Negeri 1 Air Putih Ulu, Musi Banyuasin Regency, regarding the use of Islamic animated videos as an alternative learning medium for Islamic religious education and moral character. This study was motivated by the belief that effective and meaningful learning in elementary schools requires the use of appropriate and engaging instructional materials that match students’ developmental characteristics. Islamic animated videos are considered capable of integrating relevant Islamic values into lesson content while presenting appealing visual and audio elements.This research employed a qualitative approach with a descriptive case study design to obtain an in depth understanding of the learning process. Data were collected through observation, interviews, and documentation to ensure comprehensive information. The research subjects consisted of sixth grade students, an Islamic religious education teacher, and the school principal. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation of sources and techniques.The findings show that, supported by adequate school facilities and infrastructure, teachers were able to integrate Islamic animated videos effectively into classroom learning. Compared to conventiona lecture based methods, students demonstrated more positive responses, including higher motivation, enthusiasm, active participation, and improved understanding of the learning material. The school also provided strong support for the use of this medium, considering it relevant to Islamic Religious Education and moral character. However, challenges such as power outages and network disruptions remain obstacles that hinder the optimal implementation.